The Routledge International Handbook of Creative Cognition. - Ball, Linden J. (Routledge International Handbooks Series, 2023)
This is an authoritative reference work that offers a well-balanced overview of current scholarship across the full breadth of the rapidly expanding field of creative cognition. It contains 43 chapters written by world-leading researchers, covering foundational issues and concepts as well as state-of-the-art research developments.